Tariffs and Income Distribution: Some Empirical Evidence for the United States - Burgess, David F. (Journal of Political Economy, 1976)
The duality between transformation functions and joint cost functions and 10 the generalized linear-generalized Leontief form are used to provide a framework suitable for assessing the income distributional effects of tariffs. Imports are viewed as intermediate inputs which are combined with capital and labor by the aggregate private domestic producing sector to produce two composite outputs for final demand. The manner by which higher tariffs affect factor rewards depends critically upon whether the technology is separable or nonjoint. Both of these popularly used special cases are shown to be of questionable empirical validity for the postwar U.S. economy. Nevertheless, both models predict that higher tariffs raise real wages.